2014
DOI: 10.1212/wnl.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate in skeletal muscle fatty acid oxidation disorders

Abstract: This study provides Class I evidence that bezafibrate 200 mg 3 times daily is ineffective in improving changes in FAO and HR during exercise in adults with CPT II and VLCAD deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 24 publications
0
54
1
1
Order By: Relevance
“…Finally, investigation of the role of mitochondrial targeted antioxidants or compounds that increase mitochondrial biogenesis and dynamics, such as resveratrol and bezafibrate, firstly in Gcdh‐/‐ mice tissues and cells from patients affected by GA I, may represent in the future novel therapies aiming to reduce reactive species levels and improve cellular respiration in this disease. In this particular, beneficial effects of these compounds have been demonstrated in animal models and fibroblasts from patients with fatty acid oxidation and respiratory chain defects (Bonnefont et al, 2009; Aires et al, 2014; Ørngreen et al, 2014; Djouadi and Bastin, 2019). We expect that this review article may encourage additional investigations in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, investigation of the role of mitochondrial targeted antioxidants or compounds that increase mitochondrial biogenesis and dynamics, such as resveratrol and bezafibrate, firstly in Gcdh‐/‐ mice tissues and cells from patients affected by GA I, may represent in the future novel therapies aiming to reduce reactive species levels and improve cellular respiration in this disease. In this particular, beneficial effects of these compounds have been demonstrated in animal models and fibroblasts from patients with fatty acid oxidation and respiratory chain defects (Bonnefont et al, 2009; Aires et al, 2014; Ørngreen et al, 2014; Djouadi and Bastin, 2019). We expect that this review article may encourage additional investigations in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Significant long-term symptoms have been reported in patients identified both symptomatically and through newborn screening. Improvement in these symptoms with the use of the investigational drug triheptanoin has been reported [10, 14], but not with bezafibrate [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Yasuno et al demonstrated an increased enzymatic activity following bezafibrate treatment in human induced pluripotent stem cell-derived myocytes obtained from a Japanese patient with CPT II deficiency (8). In contrast, Ørngreen et al found no significant improvement of bezafibrate treatment in a randomized clinical trial of patients with CPT II deficiency and very long-chain acyl-CoA dehydrogenase deficiencies, which put into question the effectiveness of bezafibrate in vitro and in vivo (9). However, the general effectiveness of combination therapy similar to that applied in our case remains to be determined.…”
Section: Discussionmentioning
confidence: 99%